Comparison of Surgical Outcomes Between Anterior Fusion and Posterior Fusion in Patients With AIS Lenke Type 1 or 2 that Underwent Selective Thoracic Fusion -Long-term Follow-up Study Longer Than 10 Postoperative Years. Issue 21 (November 2015) - Nohara, Ayato; Kawakami, Noriaki; Saito, Toshiki; Tsuji, Taichi; Ohara, Tetsuya; Suzuki, Yoshitaka; Tauchi, Ryoji; Kawakami, Kazuki
Abstract : Study Design: A retrospective comparative study. Objective: We compared the outcomes between patients treated either by selective thoracic anterior (ASF) or posterior spinal fusion (PSF), with a minimum 10-year follow-up. Summary of Background Data: A retrospective long-term follow-up study was conducted to compare PSF (P group) and ASF (A group) with Lenke type 1 or 2. There were no significant differences in the correction rate and incidence of degenerative discs (DDs) on the lumbar area. Loss of correction was greater in the A group. Methods: The inclusion criteria were female, AIS Lenke type 1 or 2, minimum 10-year follow-up, MRI check-up at 5 years and 10 years postop. The number of patients, age, and curve types at the time of surgery were matched in both groups. Complications, pulmonary function, and SRS-30 were also evaluated. Results: P group: adding-on (AO) occurred in 14 patients. Two patients demonstrated progression of scoliosis >5° during follow-up. Degenerative discs occurred in 43% of patients at 10 years postop. There were significant differences in the %VC and FVC before surgery and at the final visit ( P < 0.05). A group: AO occurred in 16 patients. Eleven showed progression of scoliosis >5°. Degenerative disc was recognized in 53% of the patients. There was no significant difference in the pulmonary function. There was a significant difference in selfimage score in the SRS-30 between the two groups ( P < 0.05). Conclusion: Correction of scoliosis was significantly better ASF than PSF immediately postop. Greater loss of correction occurred with ASF at postop 10 years. Although shorter segments could be fused by ASF, there was no significant difference in the incidence of DDs. Pulmonary function test results improved in the P group and were restored in the A group during the perioperative period.